Graduated guidance delivered by parents to teach yoga to children with developmental delays. Issue 1 (24th September 2015) - Gruber, Deborah J.; Poulson, Claire L.
Abstract : We evaluated the effects of a parent‐implemented intervention to teach yoga poses to 3 children with developmental delays. Graduated guidance, provided by the participants' mothers, was introduced in a multiple baseline design across the participants. With the introduction of intervention, imitation of the response chains increased over baseline for all participants. Generalization to novel and live models occurred for 2 participants. Results are discussed in terms of using behavior‐analytic procedures to teach physical fitness activities to individuals with developmental disabilities.